Isolation and Drug Sensitivity of Extended Spectrum Beta Lactamase (ESBL) Uropathogens - Ejaz Ahmed , Saira Bugti ,Altaf Ahmed Shaikh,MehreenEjaz ,Shaheen Javed (Journal of Rawalpindi Medical College, 2015)
Background: To isolate and analyze drug sensitivity of Extended Spectrum Beta Lactamase (ESBL) Uropathogens Methods: A total number of 500 urine samples were processed. Out of these 250 were positive on culture.Antimicrobiol susceptibility testing was performed by Kirby Bauers disc diffusion method. Isolates resistant to third generation cephalosporins were tested for ESBL production by double disk synergy test method. An Oxide combination disc and the equivalent single Cephalosporin disc were placed on the plate. ESBL detection was carried out by a double disc diffusion method of Jarlieret al. Results: Escherichia coli (34.0%) was the commonest, followed by Klebsiella species (16%), Staphylococcus saprophyticus (12.0%), Proteus (9.60%), Staphylococcus epidermidis (9.20%), Staphylococcus aureus (8.4%), Pseudomonas species (7.20%), Enterobacter (2.0%) and Enterococci (1.6%). Out of all these, the two principal isolates which were ESBL producing organisms were E. Coli (20%) and Klebsiella species (30%). They also showed multidrug resistance to quinolone derivatives and third generation cephalosporin groups of drugs.There were total fifty (50) organisms which were ESBL producing isolates. Conclusion: The ESBL producing organisms are resistant to third generation cephalosporins and also other antibiotics like quinolone derivatives . Antibiotics of choice for infections by ESBL producing organisms are the carbapenems.